Preliminary Results Regarding the Growth of Catfish in Floating Cages on the Irrigation Canal - Elena Sîrbu; Veta Nistor; Floricel Maricel Dima; Neculai Patriche; Liliana Blondina Athanasopoulos; Magdalena Tenciu (Scientific Papers Animal Science and Biotechnologies, 2023)
The selection of fish species that can be raised in floating cages took into account the physiological compatibility between them and the water supply to the irrigation canal, respectively of the Danube River. The European catfish is a predatory species with a positive growth rate and high-quality meat, which recommends it for use in aquaculture. This experiment aimed to adapt and evaluate the growth conditions of wels catfish (Silurus glanis, Linnaeus 1758) in floating cages located on the irrigation canal. The experimental period lasted 120 days. A number of 52 catfish specimens were distributed in two floating cages, the experimental variant V1 with 26 specimens and an average weight of 230 g, and the experimental variant V2 with 26 specimens and an average weight of 440 g. The fish were fed three meals per day with extruded feed containing 53% crude protein and 18% fat. The analysis of the experimental data on the growth of catfish in floating cages located in irrigation canals shows that both, the survival of the biological material and its growth rate, registered a positive evolution in the experimental variant V2, where survival was 92% and gained weight 19.66 kg/m3, compared to 12.12 kg/m3 in the experimental variant V1. In conclusion, catfish may be a species of interest for the culture in floating cages on irrigation canals, but the study recommends future research to elucidate several aspects of growing and assessing of the environmental conditions.